1655 - Frontispiece of Museum Wormiani Historia - Didier Descouens (Wikimedia Commons, 2019)
Notice iconographique issue de Wikimedia Commons. Titre: 1655 - Frontispiece of Museum Wormiani Historia. "Musei Wormiani Historia," the frontispiece from the Museum Wormianum depicting Wormius' cabinet of curiosities, 1655
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures